Growth in early life is associated with altered gene expression, DNA methylation and body composition in childhood. (29th September 2015) - Groom, A; Embleton, N; Korada, M; Swan, D; Cordell, H; Mathers, J; Relton, C
Abstract : Background: Nutrient-mediated molecular changes in early life may influence gene expression, produce persisting functional change, and involve epigenetic mechanisms. Such events may cause aberrant epigenetic marking and precipitate altered expression of specific genes resulting in changes in body composition in childhood. Objective: Transcriptomic analysis of preterm-born children aged 10–12 years, grouped by early life growth velocity. Genes demonstrating differential expression were assessed for differential methylation and association with childhood phenotype. Design/Methods: Gene expression analysis (Affymetrix whole genome microarray) on peripheral blood RNA from 12 low thrive (change in Z weight term to term+12 weeks) and 12 high thrive children selected from a larger cohort (n=136). Anthropometric, biochemical and nutrient markers in early life and 10–12 years were collected. DNA and RNA analysis was performed using whole blood (age 10–12 years). Sex specific analysis was undertaken due to the gender dichotomy commonly observed in developmental programming. A panel of differentially expressed genes were further investigated to see if DNA methylation of CpG rich promoter regions were noted. Analysis of TACSTD2 methylation by Pyrosequencing following bisulphite modification is reported. Seven CpG sites, −467 to −427 from the transcription start site, within the CpG island of the predicted promoter region were analysed. Results: 245 loci were upregulated in low vs high thrive females and 352 in low vs high thrive males, with 28 being common to both sexes. Of these genes TACSTD2 was selected for further investigation. TACSTD2 was upregulated (2.6-fold in males; 4.1-fold in females) in low thrive compared to high thrive (p<0.0001). DNA methylation of the TACSTD2 promoter was inversely correlated with gene expression (−0.89, p<0.0001). Higher levels of DNA methylation were associated with lower fat mass (p trend = 0.03). Conclusion: Children born preterm with different early postnatal growth patterns display considerable differences in gene expression levels and gene-specific DNA methylation levels at age 10–12 years. These data provide proof of principle in a human cohort of programmed changes in gene expression which are associated with early life exposures and may be mediated by epigenetic mechanisms. Furthermore, we provide limited evidence of an association between methylation status and body composition in childhood.